Protein-based SARS-CoV-2 spike vaccine booster increases cross-neutralization against SARS-CoV-2 variants of concern in non-human primates - Pavot, Vincent; Berry, Catherine; Kishko, Michael; Anosova, Natalie G.; Huang, Dean; Tibbitts, Tim; Raillard, Alice; Gautheron, Sylviane; Gutzeit, Cindy; Koutsoukos, Marguerite; Chicz, Roman M.; Lecouturier, Valerie (Nature communications, 2022)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants that partly evade neutralizing antibodies raises concerns of reduced vaccine effectiveness and increased infection. We previously demonstrated that the SARS-CoV-2 spike protein vaccine adjuvanted with AS03 (CoV2 preS dTM-AS03) elicits robust neutralizing antibody responses in naïve subjects. Here we show that, in macaques primed with mRNA or protein-based subunit vaccine candidates, one booster dose of CoV2 preS dTM-AS03 (monovalent D614 or B.1.351, or bivalent D614 + B.1.351 formulations), significantly boosts the pre-existing neutralizing antibodies against the parental strain from 177- to 370-fold. Importantly, the booster dose elicits high and persistent cross-neutralizing antibodies covering five former or current SARS-CoV-2 variants of concern (Alpha, Beta, Gamma, Delta and Omicron) and, unexpectedly, SARS-CoV-1. Interestingly, we show that the booster specifically increases the functional antibody responses as compared to the receptor binding domain (RBD)-specific responses. Our findings show that these vaccine candidates, when used as a booster, have the potential to offer cross-protection against a broad spectrum of variants. This has important implications for vaccine control of SARS-CoV-2 variants of concern and informs on the benefit of a booster with the vaccine candidates currently under evaluation in clinical trials. Emerging SARS-CoV-2 variants of concern (VOCs) raise questions on vaccine effectiveness. Here, the authors show that an adjuvanted protein-based SARS-CoV-2 spike vaccine booster increases cross-neutralization of VOC, including omicron, in non-human primates.